Molecular and carbon isotope composition of hydrocarbons from ambers of the Eocene Shenbei coalfield (Liaoning Province, NE China). (August 2022) - Liu, Bangjun; Bechtel, Achim; Gross, Doris; Zhao, Qiaojing; Guo, Wenmu; Ajuaba, Stephen; Sun, Yuzhuang; Zhao, Cunliang
Highlights: Amber layers and particles were found in the Shenbei lignite deposit. Ambers within Eocene Shenbei lignite originated from gymnosperms ( Taxodium, Pinus ) Diterpenoids in the ambers improve botanical information during Eocene in NE China. The δ 13 C values of terpenoid biomarkers help delineate diagenetic pathways. High δ 13 C values of diterpenoids reflect decreased MAP during middle-upper Eocene. Abstract: The molecular and (bulk and compound-specific) stable carbon isotope composition of ambers from the Shenbei coalfield, northeastern China, were analysed to determine their origin and palaeobotanical affinitions. The applicability of the δ 13 C data of saturated diterpenoid hydrocarbons for palaeoenvironmental reconstruction was addressed by comparison with published carbon isotope ratios of diterpenoids from adjacent areas. The detected sesquiterpenoids are common biomarkers for the gymnosperm families of Pinaceae and Cupressaceae. The diterpenoids dominate the saturated hydrocarbon fraction with high abundances of kaurane-type compounds. Abietane-type, cadalene-type and alkylated compounds are the main biomarkers in the aromatic hydrocarbons in the ambers. Proposed typical biomarkers for amber (e.g., amberene and homoamberene) have also been detected and probably derived from the diagenesis of the abietane-type terpenoids in the studied ambers. The biomarker composition suggest that the ambers probably originated from gymnosperms such as Taxodium and Pinus . The δ 13 C values of bulk amber and individual compounds fall within the range of ancient ambers, but the δ 13 C values of bulk amber are isotopically more enriched than modern ambers. The δ 13 C values of compounds in hydrocarbon fractions vary in broad ranges. In the saturated hydrocarbon fraction, the δ 13 C value of sesquiterpenoids (–28.0‰ to –24.5‰) fluctuates more than that of diterpenoids (–22.5‰ to –21.8‰), and the average δ 13 C value of the latter is approximately 4‰ higher than the former. Aromatic hydrocarbons are on average enriched in 13 C by around 2‰ compared to the δ 13 C of non-aromatic compounds, the result is influenced by isotopically light sesquiterpenoids in the saturated fraction. The similar carbon isotope compositions of aromatic abietane-type compounds and abietane confirm that progressive aromatization does not have a significant impact on the δ 13 C value of compounds. The obtained higher δ 13 C values of saturated diterpenoids in contrast to that of lower Eocene lignite from the nearby regions provide evidence for growth of the precursor plants of the amber in dryer habitats or differences in precipitation distribution between different locations and ages.